EFFECTIVENESS OF STP ON KNOWLEDGE REGARDING PREVENTION OF “TORCH” INFECTIONS DURING PREGNANCY AMONG ANTENATAL MOTHERS IN A SELECTED HOSPITAL AT KURNOOL (International Journal of Food and Nutritional Sciences, 2022)
All of the TORCH infections can affect people of any age or sex. However, the term TORCH is only used when it applies to pregnant women and their unborn or newborn children. As a group, TORCH infections represent a common cause of birth defects. They can cause still births in the delivery of a dead baby. In this study evaluative approach and true experimental pre test post test was used. Total 60 samples were in these study 30 experimental and 30 control group